1994
DOI: 10.2337/diacare.17.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Lipoprotein Composition by Intraperitoneal Insulin in IDDM: Role of increased hepatic lipase activity

Abstract: The increased activity of hepatic lipase after intraperitoneal insulin administration in IDDM patients appears to be one of the main determinants of lipoprotein changes observed, resulting in the normalization of lipoprotein composition during this mode of therapy. The normal inverse relationship between VLDL triglycerides and HDL cholesterol, which was not present in IDDM patients with subcutaneous therapy, was restored with intraperitoneal insulin regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
4

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 31 publications
(41 reference statements)
4
39
1
4
Order By: Relevance
“…46 ' 47 When this type of technology was applied and both fasting and 24-hour free insulin levels were lowered, we did in fact observe a decline in the absolute and specific activity of LPL. In addition, we found a trend toward increases in HTGL during IP treatment, suggesting that IP insulin delivery may have stimulated the activity of hepatic lipase as Ruotolo et al 48 have reported in similarly treated IDDM patients. It is also possible that IP insulin increased the metabolic clearance rate of LPL.…”
Section: Discussionsupporting
confidence: 80%
“…46 ' 47 When this type of technology was applied and both fasting and 24-hour free insulin levels were lowered, we did in fact observe a decline in the absolute and specific activity of LPL. In addition, we found a trend toward increases in HTGL during IP treatment, suggesting that IP insulin delivery may have stimulated the activity of hepatic lipase as Ruotolo et al 48 have reported in similarly treated IDDM patients. It is also possible that IP insulin increased the metabolic clearance rate of LPL.…”
Section: Discussionsupporting
confidence: 80%
“…Alternatively, a low VLDL triglycerides : apoB ratio could be attributable to increased lipoprotein lipase (LPL) activity. However, in several studies, type 1 diabetic patients and control subjects have been shown to have similar levels of LPL activity [22][23][24]. Moreover, if LPL activity were increased in type 1 diabetes mellitus, VLDL catabolism would be expected to be accelerated; however, this was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 59%
“…Although VLDL subfractions and hepatic lipase activity were not measured in our study, it seems reasonable that similar changes explain the differences we found in postprandial lipaemia between insulin aspart and repaglinide treatment as both repaglinide and sulphonylureas are considered to exclusively act as insulin secretagogues [44]. In a study by Ruotolo et al intraperitoneal insulin administration to patients with type 1 diabetes increased hepatic lipase activity, which is in support of this concept [45]. Our results showed a tendency towards lower postprandial FFA levels during insulin aspart than during repaglinide treatment, which suggest a decrease in FFA flux to the liver causing a lower hepatic TG production.…”
Section: Discussionsupporting
confidence: 83%